(untitled) (International Journal of Agricultural Research, Innovation and Technology, 2025)
This study aimed to assess the physicochemical quality of water, the presence of toxic heavy metals, and the associated ecological risk in the trans-boundary of the Someshwari River as it enters Bangladesh through Netrokona District. Samples were collected over the period from June 2021 to May 2022 from five distinct locations. The investigation examined the current status of various physicochemical parameters of the water, including color, odor, temperature, dissolved oxygen (DO), biological oxygen demand (BOD), electric conductivity (EC), total dissolved solids (TDS), and alkalinity, as well as the concentrations of heavy metals (Pb, Cd, Cr, Cu, and Mn). The findings of the study revealed that temperature, pH, DO, BOD, TDS, EC, and total alkalinity were within established standard limits. The pH values across all water samples exhibited variation within the range of 7.60 to 7.80. Additionally, the concentrations of Pb, Cd, Cu and Mn were found to be within acceptable levels. Notably, no detectable levels of Cr were identified in the river water throughout the three seasons. The HPI values were within the acceptable range, with a range of 42.68 to 92.10 during the pre-monsoon, 26.60 to 48.71 during the monsoon, and 5.57 to 98.00 during the post-monsoon seasons, respectively. Similarly, the HEI values indicated a low level of contamination, with variations from 0.21 to 20.30 in the pre-monsoon, 0.63 to 22.27 in the monsoon, and 5.01 to 33.12 in the post-monsoon seasons, respectively. Mean CD values consistently indicated a lower level of pollution across all three seasons. In summary, the results of this investigation suggest that the water quality in the designated area is suitable for various uses. However, to maintain this water quality, it is strongly recommended that effective awareness programs be implemented to prevent water pollution. Int. J. Agril. Res. Innov. Tech. 14(2): 44-52, December 2024